The two lives of Aleksandr Andreevič Arhangel΄skij and Aleksandr Vasil΄evič Nikol΄skij: The fates of masters of Russian sacred music in a pivotal era - Zvereva Svetlana Georgievna (Muzikologija)
This article delineates the main developments of Russian choral music in the late nineteenth and the early twentieth centuries by examining the lives of Aleksandr Andreevič Arhangelʹskij and Aleksandr Vasilʹevič Nikolʹskij. It considers transformations in the choral landscape during the pivotal years of the February and October revolutions in Russia and subsequently in the Soviet period. It highlights the circumstances in which Russian sacred music found itself in the new state and reveals how, in part thanks to Arhangelʹskij and Nikolʹskij, traditional practices were sustained - both within the USSR and among the Russians abroad.